Judicious use of redundant transmissions in multichannel ALOHA networks with deadlines. - Birk, Y. (IEEE Journal on selected areas in communications)
This paper shows how to improve the classic multichannel slotted ALOHA protocols by judiciously using redundant transmissions. The focus is on user-oriented requirements: a deadline along with a permissible probability of failing to meet it. Subject to satisfying those, maximization of capacity is the optimization goal. When there is no success/failure feedback prior to the deadline, the use of information dispersal with some redundancy provided by error-correcting codes for the data in conjunction with a replicated, separately transmitted synchronization preamble, is proposed. It is shown to sharply reduce the overhead resulting from the use of shorter packets and to significantly increase the capacity. When the deadline permits several transmission-feedback rounds, we propose a novel replication-based retransmission policy: all attempts except the final one entail the transmission of a single or very few copies, and a larger number of copies are transmitted in the final attempt. This sharply increases channel capacity, even with a single transmitter per station. The proposed approaches are particularly suitable for high-bandwidth satellites with on-board processing